Navidezna prebavljivost surovih beljakovin in surovih maščob pri linijah miši selekcioniranih na višji oziroma nižji odstotek telesnih maščob - Trebušak, Tina (Acta agriculturae Slovenica, 2009)
Obesity and increasing of body mass index (BMI) present a growing health problem and are also an unwanted component of growth in domestic animals. The main objective of this study was to examine the effect of obesity on apparent digestibility of diet crude protein and fat in mice. In two susequent experiments digestibility was compared between two selection mouse lines, F line (selected for higher percentage of body fat) and L (selected for lower percentage of body fat). In the first experiment 21 males of both lines (11 F and 10L) between 9.0 and 18.6 weeks of age were used whereas the second experiment involved 23 males (11 F and 12 L) between 9.6 and 11.0 weeks of age. Weights of mice, faeces and food intake were recorded daily for 5 successive days. Using Weende analysis the content of crude protein and crude fat in diet and faeces were determined. The results of our study revealed statistically significant differences in the apparent digestibility of crude protein and crude fat between the F and L line. There were also significant differences in diet intake per g of body weight, but not in the total amount of all consumed diet between the lines. The crude protein and the crude fat were digested more efficiency by the L line (79.6% and 91.8%, respectively) while the F line digested 77.1% of crude protein and 87.0% of crude fat. Considering these results the differernces in the apparent digestibility of crude protein and crude fat can not explain great differences in obesity between the F and L line.
Keywords: domače živali; food; prehrana; zamaščenost; debelost; prebavljivost